A criatividade e a organiza????o do processo criativo da escrita em sala de aula - Albernaz, Karana Martins Machado (2017)
Creativity is an inherent process of human development. The creative processes emerge in the action contexts of the individual, and through subjective resources historically constituted, organize themselves in the moment of the concrete action, characterizing the creative learning of writing. Learning and its meanings embrace the educational objectives and their actions in the concrete scope of the school environment. The classroom is the ideal enrivonment for diversity where the references of how to teach must be in unison with the learning process of the students, so that, when reached at full potential, the affective, cognitive, psychomotor, relational and creative dimensions of learning are fully experimented and lived in their academical path. The syllabus is a document that matches the school with its thoeritical options, its objectives, its principles and methodologies to be applied. Transposing the perspective of individuals and their world through its community, and sharing its own educational actions.This paper intends to investigate the development of the creative writing process in the academic context, identifying, through means of indicators of creative writing, productions that represent significant results to this subject. Characterized by a qualitativeexploitational approach in addition to the use of case study. This paper utilizes the documental research, the interview and the observation as data research instruments. The data analysis, as a study strategy, is done through content analysis. As a result, the research showed that it is possible to stimulate and develop creative writing learning as long as the academic environment is in favor of it. As future pursues for studies yet to come, it will be possible to investigate the learners' perspective about creative writing learning and their text production routine, considering the activities developed inside the classroom are done with the intent of stimulating this sort of learning.